Решите уравнение
-4х-9=6х
-3х+3=-7х
-2х-4=3х
4х+10=5х
3х+3=5х
5х-6=-3х
-3х-9=2х
2х+1=-2х
-7-2х=-6х+10
2+3х=-7х-5
-1-10х=-9х+1
7+8х=-2х-5
7+9(4х+5)=-2
-5+2х=-2х-3

1

Ответы и объяснения

2014-04-13T11:44:39+04:00
-4х-9=6х
-4х-6х=9
-10х=9
х= 9/( -10)
х = - 0,9


-3х+3= -7х
-3х+7х = -3
4х= 3
х =0,75

-2х-4= -3х
-2х+3х = 4
х = 4


4х+10=5х
4х-5х = -10
-х = -10
х = 10

3х+3 = 5х
3х - 5х = -3
-2х = -3
х = 1,5

5х -6 = -3х
5х+3х = 6
8х= 6
х=0,75

-3х-9= 2х
-3х-2х= 9
-5х= 9
х= 1,8


2х+1= -2х
4х = -1
х = - 0,25



-7-2х = -6х +10
-2х+6х = 10+7
4х = 17
х=4,25


2+3х = -7х -5
3х+7х = -5-2
10х = -7
х = - 0,7

-1-10х = -9х+1
-10х+9х = 1+1
-х= 2
х = -2

7+8х = -2х-5
8х+2х = -5-7
10х= -12
х= -1,2

7+9( 4х+5) = -2
7 + 36х+45 = -2
36х = -2-7-45
36х = -54
х = -1,5

 -5+2х = -2х-3
2х+2х = -3 +5
4х= 2
х=0,5